2011
DOI: 10.1111/j.1751-7133.2011.00242.x
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Impairment in Patients With Advanced Heart Failure and Its Implications on Decision-Making Capacity

Abstract: Cognitive impairment (CI) is a multifaceted entity that entails more than just memory loss. Deficits in other domains, most importantly executive function, can have profound effects on health outcomes in afflicted patients. The prevalence of CI among the heart failure population is exceedingly high, and even higher so among patients with advanced heart failure (AHF). These patients display consistent declines in memory, attention, psychomotor abilities, and executive function. Such deficits interfere with pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 22 publications
0
39
0
3
Order By: Relevance
“…Neurocognitive deficits after transplantation are important because intact neurocognitive functioning is critical for decision-making capacity and for the ability to manage a complex medical regimen, both of which are essential elements of post-transplant care (28). Moreover, studies of other medical patients have suggested that neurocognitive deficits in executive function, memory, and working memory are associated with poorer medication adherence (5,(29)(30)(31), including patients with HIV (31-33) and cardiovascular disease (5) and healthy older adults (29).…”
Section: Discussionmentioning
confidence: 99%
“…Neurocognitive deficits after transplantation are important because intact neurocognitive functioning is critical for decision-making capacity and for the ability to manage a complex medical regimen, both of which are essential elements of post-transplant care (28). Moreover, studies of other medical patients have suggested that neurocognitive deficits in executive function, memory, and working memory are associated with poorer medication adherence (5,(29)(30)(31), including patients with HIV (31-33) and cardiovascular disease (5) and healthy older adults (29).…”
Section: Discussionmentioning
confidence: 99%
“…Impaired cognition contributes to factors that lead to poor outcomes of older women with HF by reducing decision-making capacity and complicating HF self-management in this group. Specifically, cognitive deficits interfere with the ability to recognize and respond to worsening symptoms, follow complex medication regimens and adhere to diet and fluid restrictions [92,93]. Older women report more functional limitations, anxiety and depression than men at older ages [102], thus contributing to double jeopardy situations associated with poor outcomes in those with HF [11,90,92].…”
Section: Aging and Hfmentioning
confidence: 99%
“…Uncommon in persons aged younger than 50 years, CHF becomes more prevalent with increasing age and affects 6-10% of the population aged 65 years and older (2). CHF impairs patients' quality of life, physical health and functioning, as well as cognitive health (3)(4)(5). Besides hypertension, ischemic heart disease and atrial fibrillation, a frequent comorbidity in CHF is anemia (6).…”
Section: Introductionmentioning
confidence: 99%